The Effect Of Sowing Rate And Period On The Fertility Of Ryjik Seeds - G.Uzakov; D.Allayeva (Genius Journals, 2023)
In the article, the effect of planting period and standards on the germination of autumn camelina varieties grown in light gray soils of Kashkadarya region and the number of plants germinated per 1 m2 area was studied and analyzed.
Keywords: Camelina; seeds; seeding rate; sowing time